Differentiated effects of COVID-19 on university students - Mercado, Ricardo (2022)
The confinement due to the coronavirus had effects after implementing virtual education at all educational levels. To identify the students' perception about the teaching-learning conditions that prevailed during COVID-19, distinguishing those that allowed them to continue learning from those that did not work in the academic areas of higher education in health sciences. And economic-administrative, exploratory, descriptive and correlational research was carried out with students from the Universidad Veracruzana de México. The sample consisted of 665 non-probabilistic and non-random with a general population. It was inquired about the teacher's teaching activities, learning, academic interaction, digital knowledge, new understanding acquired, socio-emotional difficulties experienced and management strategies, and the technological resources and connectivity used. Among other results, it was found that students from the first semesters and women were the populations most likely to put metacognitive skills into practice.